209k views
1 vote
What is the answer i really need help
2x-7+-9x+81

1 Answer

4 votes

Your expression seems a little incomplete. It seems you mean to ask


2x-7+\left(-9x\right)+81=0

So, I am solving the question based on this, which anyways will solve your query.

Answer:

Please check the explanation.

Explanation:

Given the expression


2x-7+\left(-9x\right)+81=0


\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a


2x-7-9x+81=0


\mathrm{Group\:like\:terms}


2x-9x-7+81=0


\mathrm{Add\:similar\:elements:}\:2x-9x=-7x


-7x-7+81=0


\mathrm{Add/Subtract\:the\:numbers:}\:-7+81=74


-7x+74=0


\mathrm{Subtract\:}74\mathrm{\:from\:both\:sides}


-7x+74-74=0-74


-7x=-74


\mathrm{Divide\:both\:sides\:by\:}-7


(-7x)/(-7)=(-74)/(-7)


x=(74)/(7)

Therefore, the answer is:


  • x=(74)/(7)

User Muzer
by
6.5k points